Comparative analysis of breast cancer characteristics in young premenopausal and postmenopausal women in Ghana - Kingsley Bosompem; Joseph Yorke; Tonnies Abeku Buckman; Samuel Gyasi Brenu; Michael Nyantakyi; Francis Somiah-Kwaw Aitpillah; Ishmael Kyei; Michael Ofoe Adinku; Dennis Afful Yorke; Christian Obirikorang; Emmanuel Acheampong (Scientific Reports, 2024)
Abstract Breast cancer is increasingly common among young women in Ghana. BCa is heterogeneous with unique traits that impact causes, prognostic, and predictive outcomes of patients before and after menopause. However, limited evidence exists on differences between young premenopausal (YPM) and postmenopausal cases in Ghana. This study compared breast tumour characteristics between YPM women (under 35 years) and postmenopausal women. We conducted a prospective cross-sectional study involving 140 BCa-diagnosed women at the Breast Care Clinic of Komfo Anokye Teaching Hospital (KATH), Kumasi from November 2019 to June 2021. Thirty-one (22.1%) of participants were YPM and 109 (77.9%) were postmenopausal. The median ages for YPM and postmenopausal were 32.0 (range: 25.0–35.0) and 57.0 (48.0–86.0) respectively. Invasive carcinoma was the most common histological type (97.1%). Left tumour location was the most frequent in both groups (51.6% for YPM and 51.8% for postmenopausal). Lumps detected were frequently in the outer upper quadrant in both groups (61.3% and 56.0%). The majority of the YPM women (80.7%) and postmenopausal women (87.0%) had stage III and IV diseases. Most YPM (64.5%) and postmenopausal women (64.4%) exhibited triple-negative breast cancer (TNBC). Both YPM 13 (56.6%) and postmenopausal participants 40 (56.3%) exhibited a predominantly partial response to neo-adjuvant chemotherapy but YPM women (21.7%) experienced disease progression than the postmenopausal women (12.7%). The study highlights consistent tumour characteristics and advanced clinical stages at diagnosis in both groups with a higher prevalence of TNBC. TNBC and HER2+ subtypes respond better to Anthracycline-based neoadjuvant chemotherapy. Establishing Breast Care Clinics in district and regional hospitals for early detection is crucial and further studies are warranted to understand the higher TNBC prevalence in black Africans and re-evaluate breast education programs to address the persistently late presentations.